2014
DOI: 10.2174/1566524014666140724101035
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of H19 Enhances Differentiation Capacity to Epidermis of Parthenogenetic Embryonic Stem Cells

Abstract: Parthenogenetic embryonic stem (pES) cells are pluripotent stem cells derived from artificially activated oocytes without embryo destruction, thus eliciting less ethic concerns, and have been demonstrated promising for autologous stem cell therapy. However, pES cells could carry inappropriate imprinting such as relatively high expression of H19, a paternal imprinted gene, and may negatively influence their lineage differentiation. We show that knockdown of H19 by shRNA in mouse pES cells does not alter self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In RWPE-1 cell line, H19 could confer stemness phenotype by these multiple pathways. In addition, knockdown of H19 in parthenogenetic embryonic stem cells (pES) promotes differentiation of pES to epidermis, showing that H19 RNA contributes to stem cell integrity [55].…”
Section: S-shipmentioning
confidence: 99%
“…In RWPE-1 cell line, H19 could confer stemness phenotype by these multiple pathways. In addition, knockdown of H19 in parthenogenetic embryonic stem cells (pES) promotes differentiation of pES to epidermis, showing that H19 RNA contributes to stem cell integrity [55].…”
Section: S-shipmentioning
confidence: 99%
“…Recently, Yin et al . demonstrated that knockdown of H19 can improve mouse pESC differentiation potential in the lineages of ectoderm and mesoderm [ 50 ]. In further study, H19-Ifg2 and Dlk1-Dio3 imprinting region co-modification may have the greatest impact on improvement of the differentiation ability of pESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the results presented by Gabory et al confirmed that H19 played a negative role in cell proliferation [11]. Lately, it was reported that knockdown of H19 accelerated differentiation of parthenogenetic embryonic stem cells (p-ESCs) to cardiomyocytes [16, 17]. Nevertheless, little is known about the precise molecular mechanisms of H19 in cardiomyocyte differentiation.…”
Section: Resultsmentioning
confidence: 77%